Seroprevalence of fascioliasis, toxocariasis, strongyloidiasis and cysticercosis in blood samples diagnosed in Medic Medical Center Laboratory, Ho Chi Minh City, Vietnam in 2012. Issue 1 (December 2016) - Nguyen, Toan; Cheong, Fei; Liew, Jonathan; Lau, Yee
Abstract Background Despite the global effort against neglected tropical diseases (NTDs), developing countries with middle to low income are still burdened by them. Vietnam has been undergoing substantial economic growth and urbanization, but underprivileged people living in rural and suburban areas are still having little access to public health infrastructure and proper sanitation. Hitherto, limited information is available for seroprevalence and risk factors of several parasitic diseases in Vietnam. Methods A retrospective study was performed on diagnostic results ofFasciola spp., Toxocara spp., Strongyloides stercoralis andTaenia solium IgG ELISA tests from Medic Medical Center Laboratory, Ho Chi Minh City in 2012. The data were first stratified before statistical analyses were performed. Seroprevalence of fascioliasis, toxocariasis, strongyloidiasis and cysticercosis was determined and the age and gender risk factors were evaluated. Results Seroprevalence of fascioliasis, toxocariasis, strongyloidiasis and cysticercosis was 5.9 % (590/10, 084; 95 % CI: 5.44–6.36), 45.2 % (34, 995/77, 356; 95 % CI: 44.85–45.55), 7.4 % (3, 174/42, 920; 95 % CI: 7.15–7.65) and 4.9 % (713/14, 601; 95 % CI: 4.55–5.25), respectively. Co-exposure to multiple parasites was detected in 890 males (45.7 %; 95 % CI: 43.49–47.91) and 1, 059 females (54.3 %; 95 % CI: 52.09–56.51). Social structure and differences in behavioural factors caused the gender factor to have a significant effect on the prevalence of all the diseases, while the seropositivity for fascioliasis and strongyloidiasis were age group-related. Conclusions The seroprevalence of fascioliasis, toxocariasis, strongyloidiasis and cysticercosis in the blood samples diagnosed in Medic Medical Center Laboratory, Ho Chi Minh City, in year 2012 were comparatively high. The Vietnamese customs and cultures, dietary habits and agricultural practices exposed them to high risk of contracting NTDs. Despite the possibility of false positive results due to antigenic cross-reactions, detection of IgG antibodies remains as a reliable method in sero-epidemiological study as it is non-invasive and demonstrates previous exposure of individuals to the parasites. Besides the implementation of strategies to control these diseases, epidemiological analysis and surveillance of diseases should also be continually strengthened to monitor the effectiveness of regimens and interventions.